A comparative study of bacteria presence between two types of cow powdered milk/ Yanti Yaacob ... [et al.] - Yaacob, Yanti; Zulkifli, Norsakina Zurina; Salleh, Nunshaimah; Fadzil, Adibatul Husna; Ali, Rosliza; Mohmad Tahirudin, Nordiana Suhada (2023)
Given their crucial roles in the ecosystem which is present everywhere, bacteria are among the most significant species. The objectives of this preliminary study is to identify the presence of bacteria in different samples of powdered milk and to identify the types of bacteria in different samples of powdered milk which are Suffy Annis and Everyday powdered milk. The study was carried out because the microorganisms in the powdered milk samples included both hazardous and beneficial bacteria, each of which serves a specific purpose in supplying the human body with the necessary vitamins. In this experiment, bacteria were isolated from samples of each powdered milk using the techniques of agar streaking and gram staining with the goal of classifying the types of bacteria that had been noticed. According to the project's findings, the bulk of the bacteria generated were in the rod-shaped Bacillus sp., which is known to be gram positive. It states that cow's milk powdered under the Everyday brand contains the majority of probiotic bacteria, living microorganisms intended to offer health advantages when taken by the body compared to Suffy Annis milk.